Zeeman splitting and spin-orbit interaction in Hg1−xCdxTe inversion layers. (10th August 2016) - Sun, Lei; Lv, Meng; Liu, Xinzhi; Xu, Yonggang; Wang, Reng; Lin, Tie; Yu, Guolin; Dai, Ning; Chu, Junhao
Abstract: We studied the suppression of the weak antilocalization (WAL) effect and the dependence of spin dynamics for a two-dimensional electron gas in the inversion layers of two different Hg1− x Cd x Te samples in the presence of in-plane magnetic field . The WAL magnetoconductance is fitted by the Golub model to acquire the variations of phase coherence time with increasing . The effective g -factors in the form of ( is the relative effective mass) at zero magnetic field and high magnetic field are obtained by investigating the electron dephasing with varying and measuring the spin splitting of the Shubnikov-de Hass oscillations, respectively. As the obtained g -factors are in accordance with the reported results, the suppression of the WAL effect can be attributed to the competition between Zeeman splitting and spin-orbit interaction rather than to the microroughness scattering.